PENGEMBANGAN BUKU CERITA BERGAMBAR UNTUK MENINGKATKAN KARAKTER BERKEBHINEKAAN GLOBAL PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS I SEKOLAH DASAR - Tri Nasti Masna; Titin Sunaryati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research was motivated by students who lacked the character of global diversity. Learning media in schools becomes an obstacle for teachers in implementing the character of global diversity. The research aims to improve the global diversity character of students with picture story books in pancasila education learning. The research used is development research using the ADDIE model. The feasibility test was carried out by three validation experts, material experts obtained a percentage of 95%, language experts obtained a percentage of 91%, media experts obtained a percentage of 96%. Media can be said to be feasible. The effectiveness of the media can also be seen from the increase in character before and after the media is given with an N-Gain score of 0,74 in the high category. It can be concluded that picture story books can improve the global diversity of students’ characters.